Wineries communication strategies: A text mining analysis - Filippo F. Fagioli; Giorgia Gallesio; Elena Viganò (Wine Economics and Policy, 2022)
The digital literacy that has developed in recent decades has resulted in internet playing an important role in the communication of wineries. Business websites, initially used as an exhibitor of products, quickly became one of the most important tools to implement communication strategies used to successfully place the wine product in a competitive market. The purpose of this study is to analyse major Italian wineries websites through textual statistics and text mining methods to provide evidence on the storytelling device adopted by these companies to promote and brand themselves. The information contained in the websites of the selected businesses in Northern, Central and Southern Italy, has been analysed in three steps. The first consisted in investigating categories with which the contents were organized, and the second step involved examining the contents' word clouds which are useful for a qualitative analysis on similarities and differences found in the three different areas. Finally, different strategies were formalized, by reconstructing the structure of concepts underlying the communication models of the wineries of the three areas examined. The results demonstrate considerably different approaches adopted by the areas. While the wineries in Central Italy focus on communication concerning the company, in the North and South, more attention is given to production methods and territory respectively. Thanks to the analysis of word clouds it was also possible to expose the construct which is the basis of narratives used by wineries, followed by the typical communication strategy of the different Italian areas.
Keywords: 330; promotion; storytelling; text mining; website; winery